Strategic misrecognition and speculative rituals in generative AI - Sun-ha Hong (Journal of Digital Social Research)
Public conversation around generative AI is saturated with the ‘realness question’: is the software really intelligent? At what point could we say it is thinking? I argue that attempts to define and measure those thresholdsmisses the fire for the smoke. The primary societal impact of realness question comes not from the constantly deferred sentient machine of the future, but its present form as rituals of misrecognition. Persistent confusion between plausible textual output and internal cognitive processes, or the use of mystifying language like ‘learning’ and ‘hallucination’, configure public expectations around what kinds of politics and ethics of genAI are reasonable or plausible. I adapt the notion of abductive agency, originally developed by the anthropologist Alfred Gell, to explain how such misrecognition strategically defines the terms of the AI conversation.